Stock Prices and Real Exchange Rate Movements in the Gulf Cooperation Council - Hassanain, Khalifa (International Journal of Economics and Financial Issues, 2017)
In this paper, we examine the interaction between stock prices and the real and nominal exchange rates in the Gulf Cooperation Council (GCC) economies (including only Kuwait (KW) and Saudi Arabia (SA). We consider the real and the nominal exchange rates of US dollar in terms of the Saudi Riyal and Kuwaiti Dinar and the values of Saudi and Kuwaiti Exchange Stock Exchange indexes. The purpose is to investigate relationship between the volatility in stock prices in these markets and the large swings in global currencies given their alternative exchange rate arrangements. Keywords: Stock prices, Exchange rate, real exchange rate JEL Classifications: F32 G15